How fast can a human run? - Richmond, J. (New Studies in Athletics, 2012)
As sprinters challenge each other to win major championships and run faster we are naturally curious if there is a limit to how far the 100m world record can fall. Predictions about how fast humans can run have been made in the past using mathematical curve fitting based on previous record-breaking performances, metabolic factors and thermodynamic principles and, particularly in the case of the 100m, information about phosphagen energy stores. In this study, the author presents a projection of the limits of human performance in the 100m based on known physiological measurements and recorded observations, many of which are recent findings. It is assumed that ground contact time limits maximum running velocity and that force production times are similar between sprinters running under 10 sec today and in recent years. From the evidence available it seems plausible that humans could reach a velocity of 12.75 m/sec compared to the 12.34 m/sec achieved by Usain Bolt (JAM) in his 9.58 sec world record race. Assuming similar velocity relationships across all phases of the race and the same start reaction time recorded for Bolt, it is suggested that the human limit for the 100m may be close to 9.27 sec.